2019
DOI: 10.1186/s40337-019-0245-3
|View full text |Cite
|
Sign up to set email alerts
|

Peer mentoring for eating disorders: results from the evaluation of a pilot program

Abstract: Background Eating disorders (EDs) are serious psychiatric illnesses that have high rates of morbidity and mortality, and low long-term recovery rates. Peer mentor programs (PMPs) have been associated with reduced psychiatric hospitalisation and shorter lengths of stay for those with other severe mental illnesses. The present study evaluated the feasibility and preliminary efficacy of a PMP for individuals with EDs in improving symptomatology and quality of life. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 26 publications
(38 reference statements)
2
49
0
Order By: Relevance
“…Consistent with prior work (Beveridge et al, ; Perez et al, ), peer mentorship appeared feasible among patients with eating disorders, based on high acceptability ratings, low dropout rate, and good attendance rate. The rate of program completion was 80%, which is comparable with 73% retention in a prior feasibility study of peer mentorship for patients with eating disorders (Beveridge et al, ).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Consistent with prior work (Beveridge et al, ; Perez et al, ), peer mentorship appeared feasible among patients with eating disorders, based on high acceptability ratings, low dropout rate, and good attendance rate. The rate of program completion was 80%, which is comparable with 73% retention in a prior feasibility study of peer mentorship for patients with eating disorders (Beveridge et al, ).…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with prior work (Beveridge et al, ; Perez et al, ), peer mentorship appeared feasible among patients with eating disorders, based on high acceptability ratings, low dropout rate, and good attendance rate. The rate of program completion was 80%, which is comparable with 73% retention in a prior feasibility study of peer mentorship for patients with eating disorders (Beveridge et al, ). Findings pertaining to attendance, feasibility, and intervention preference suggest that connecting with someone who has “been there” is a preferred treatment modality that can engender high patient engagement, which is particularly notable for patients with eating disorders, often characterized by high ambivalence about change.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These include increases in treatment motivation, hope, knowledge (insider information), and decreases in fear and stigma [ 33 , 38 , 39 ]. Potential risks could include overestimation of treatment effects [ 39 ] and maladaptive social comparisons (peer contagion effect) [ 40 , 41 ]. Nonetheless, based on the present results, it seems highly promising to further investigate the influences of successfully treated former patients (‘positive role models for treatment’) on the treatment initiation of so far untreated individuals with AN.…”
Section: Discussionmentioning
confidence: 99%
“…To address the shortcomings of the research noted above, a study of the feasibility and acceptability of a sixmonth, one-to-one peer-mentoring program (PMP) for people with eating disorders was conducted (for detailed results, see [40]). It was found that mentees involved in the program demonstrated improvements in ED symptomatology, quality of life, mood, and perceived disability.…”
Section: Introductionmentioning
confidence: 99%